Managemen Konflik Mahasiswa: Destruktifkah? - Fathul Lubabin Nuqul; Ardana Reswari Miranda Ningrum; Mochammad Sulaiman Zuhdi (Universitas Muhammadiyah Jember, 2018)
Conflict is a condition that characterized by the pull of interests. Conflict is not always result a negative effects on the individual. Accuracy in regulating the conflict determines the effects of the conflict. Johnson Johnson (2014) divides conflict management into two major classifications, such as, constructive or destructive conflict management. The aim of the study is to know the conflict management tendence in university student. The study involved 164 college students. The measurement done with conflict management conflict scale. The results showed that subjects generally have a tendency constructive conflict management. This can be shown from the average of constructive conflict management style more than in the management destructive conflict style. It means students tend to be more able to address and deal with its conflicts well. However, after review of the differences the study period, the first year students was a student of conflict tend to have a more destructive force than the students who entered the second or third study. It reveals that study in campus can be good for ability of conflict management.